ORP4L couples IP3 to ITPR1 in control of endoplasmic reticulum calcium release. Issue 12 (23rd October 2019) - Cao, Xiuye; Chen, Jianuo; Li, Dan; Xie, Peipei; Xu, Mengyang; Lin, Weize; Li, Shiqian; Pan, Guoping; Tang, Yong; Xu, Jun; Olkkonen, Vesa M.; Yan, Daoguang; et al.
Abstract : Oxysterol‐binding protein‐related protein (ORP) 4L acts as a scaffold protein assembling CD3‐ε, G‐αq/11, and PLC‐β3 into a complex at the plasma membrane that mediates inositol (1, 4, 5)‐trisphosphate (IP3 )‐induced endoplasmic reticulum (ER) Ca 2+ release and oxidative phosphorylation in T‐cell acute lymphoblastic leukemia cells. Here, we offer new evidence that ORP4L interacts with the carboxyl terminus of the IP3 receptor type 1 (ITPR1) in Jurkat T cells. ORP4L enables IP3 binding to ITPR1; a truncated construct that lacks the ITPR1‐binding region retains the ability to increase IP3 production but fails to mediate IP3 and ITPR1 binding. In association with this ability of ORP4L, it enhances Ca 2+ release from the ER and subsequent cytosolic and mitochondrial parallel Ca 2+ spike oscillations that stimulate mitochondrial energetics and thus maintains cell survival. These data support a novel model in which ORP4L is a cofactor of ITPR1, which increases ITPR1 sensitivity to IP3 and enables ER Ca 2+ release.—Cao, X., Chen, J., Li, D., Xie, P., Xu, M., Lin, W., Li, S., Pan, G., Tang, Y., Xu, J., Olkkonen, V. M., Yan, D., Zhong, W. ORP4L couples IP3 to ITPR1 in control of endoplasmic reticulum calcium release. FASEB J. 33, 13852‐13865 (2019). www.fasebj.org